Redução na oferta de transporte público em função da pandemia de COVID-19. Estudo de Caso: linhas que operam no terminal da UFPA - OTA, Vitor Hiroshi Barros (2021)
Due to the Covid-19 pandemic and the social isolation measures applied throughout this period, the mass transit sector has been facing a difficult moment. As the daily movement of the population was reduced, the mass transit had an abrupt reduction in the demand of paying users, which unbalanced the system's revenues and caused operators to also reduce the offer, in order to find the balance by reducing costs. The present work aims to identify the percentage of reduction in the travel offer of the lines that serve the Federal University of Pará (UFPA). For this, the number of actual trips made by the lines that departed or passed through UFPA's mass transit terminals was recorded in the field and later this data was compared with the number of trips programmed for the lines, according to information from the Moovit mobility application. The survey detected an average reduction of 39.4% in the amount of trips offered, and in three lines (320 / 312 / 999) there were reductions of more than 70% in the offer of trips. Among the days of the week analyzed, Sundays and holidays had the greatest reduction (51.6%) in supply. The afternoon shift showed a greater reduction in travel (44.0%) than the morning shift (29.5%). Among the 3 months analyzed, July had the greatest reduction (42.9%). The work also registered a moderate positive correlation between the length of the line and the reduction in supply, indicating that in longer lines, there is a tendency towards a greater reduction in supply. Despite these significant reductions, there was a gradual increase in supply between July and September, following the advance of vaccination and a reduction in the number of cases and hospitalizations in the city.